2018
DOI: 10.1038/s41598-018-32426-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-194-5p Levels Decrease during Deep Hypothermic Circulatory Arrest

Abstract: Hypothermia has been reported to be effective in protecting the brain in various clinical conditions, including resuscitation after cardiac arrest and complex cardiovascular surgery, and is considered to be a promising therapy for stroke. The present study aimed to confirm the pivotal role that miRNA-194-5p plays in deep hypothermia circulation arrest. On the basis of reductions in expression of miR-194-5p in the circulation of 21 aortic dissection patients who underwent deep hypothermia circulatory arrest, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…19 In vitro studies using oxygen and glucose-deprived primary neuron cultures under hypothermia showed a downregulation of ischemia tolerance-related protein SUMO2 mediated by miR-194-5p. 9 In our study, miR-194-5p was predicted to be…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…19 In vitro studies using oxygen and glucose-deprived primary neuron cultures under hypothermia showed a downregulation of ischemia tolerance-related protein SUMO2 mediated by miR-194-5p. 9 In our study, miR-194-5p was predicted to be…”
Section: Discussionmentioning
confidence: 50%
“…7 So far, the expression patterns and functions of circRNAs in the brain damage associated with DHCA remain uninvestigated, though previous studies have shown the regulatory role of miRNAs in ischemia-reperfusion, hypothermia, and inflammatory and immune responses after extracorporeal circulation. 8,9 This study aimed to reveal whether circRNAs are implicated in the brain damage after DHCA. A rat model of DHCA was established for identifying differentially expressed circRNAs in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been published on the role of miR-194-5p in CNS injury; however, one study corroborates our findings. miR-194-5p delivery into primary cortical neurons, while not directly causative of neuronal cell death, did mediate neuronal death instigated via oxygen-glucose deprivation [ 34 ]. Cortical neurons with enhanced levels of miR-194-5p were exquisitely sensitive to this form of damage.…”
Section: Discussionmentioning
confidence: 99%
“…As the expression of miR-194b-5p was significantly downregulated in the serum and small intestine of the weaned piglets, the authors hypothesized that its expression in serum may reflect the decreased expression in the small intestine. This finding is important given that miR-194b-5p has been demonstrated to downregulate the expression of small ubiquitin-like modifier 2 (SUMO2) (140). SUMO2 is pivotal for cell homeostasis during endogenous or environmental stress, including, among others, heat shock and nutrient stress (141).…”
Section: Management and Stressmentioning
confidence: 99%